Design of a Web-Based Decision Support Information System for YMM FI Scholarship Recipients Using the SMART Method - Baharuddin, Rismayada; Purwadi; Saputra, Yogi (CV. Generasi Intelektual Digital, 2024)
Designing a Web-Based YMM FI Scholarship Recipient Decision Support Information System Using the SMART Method can help YMM FI in the decision-making process to determine the right scholarship recipient. YMM FI is a zakat fund management foundation which has several programs, one of which is still running, the Edu Care Program which focuses on funding education from the lower to upper levels. However, the selection of prospective recipients of higher education scholarships is still done manually, which results in inaccuracies in those who receive them. For this reason, there is a need for a Web-Based Decision Support System using the SMART Method which takes into account several attributes that have weighted values and criteria. From the results found, attribute A2 with the name Wa Marlin is the highest ranking of the other attributes